Quantitative Performance Of Saburai Goat Breeding In Gisting District, Tanggamus Regency: Quantitative Performance Of Saburai Goat Breeding In Gisting District, Tanggamus Regency - Luthfiah Hayati; Boby Arya Putra; Riko Herdiansah; Septi Muthoharoh (JDP: Jurnal Dunia Peternakan, 2026)
Saburai goats have a high level of growth and adaptation that is derived from the seeds and broods of crossbreeds from their parents and currently the population of Saburai goats in Tanggamus Regency is starting to decrease. Thus, a study was conducted on the quantitative reproductive performance of Saburai goat breeds in Gisting District, Tanggamus Regency. The material used was 66 Saburai goat breeds. This research will use non probability sampling technique, namely saturated sampling. Reproductive data collection techniques are observation, interview, and documentation with observed data in the form of conception rate (CR), service per conception (S/C), and litter size (LS) grouped by parity (P) 1 - 4. Then analyzed using statistical tests and presented descriptively. So it can be concluded that the population of Saburai goats in Gisting sub-district as of December 31, 2024 is only 0.91% of the goat population in Gisting sub-district; S/Cand LS at parity 1 - 4 have a value of P <0.05 which indicates that in the parity of Saburai goat broods there is a significant difference between parities; CR at parity 1 - 4 have a value of P>0.05 which indicates that in the parity of Saburai goat herds there is no significant difference between parities; and the average value of CR, S/C, and LS in Saburai goat herds is in the ideal category but almost all farmers have not recorded matings and births, so performance is not in the optimum category.